Do medical students have problem with choosing the specialty? Preliminary report of the medical students population based study - Sawonik , Sebastian; Kozłowiec, Monika; Kołodyńska, Aleksandra; Domagała, Adam; Aftyka, Anna; Milanowska, Joanna; Gierszon, Patrycja; Kwika, Maria Dorota; Samardakiewicz, Marzena (Polish Journal of Public Health, 2019)
Introduction. Choosing medical specialty is one of the most crucial decisions about future career of graduates. Multiplicity and variety of available options make great opportunities for development of interests and ambitions of future doctors. Unfortunately, it can also be an impediment in making decisions about path of medical career. Aim. The aim of the study was to discover if medical students have problem with choosing specialty and to ask about availability and need of career guidance for medical students. Material and methods. Voluntary survey was conducted via the Internet among medical students in Polish and foreign medical universities. Results. The total number of 565 medical students completed the survey – 371 women (66.5%) and 189 men (33.5%). They were students of 16 medical universities, 10 Polish and 6 foreign ones. Problem with choosing medical specialization reported over 70% respondents. Only 11.9% of the group declare that they participated in classes that were helpful in making decision about their future medical career. Need for career guidance was revealed in over 91.5% answers. Significant difference between genders has been found in reporting problem with choosing medical specialty – it was reported by 75.5% of women and 62.4% of men. There were no differences between the Polish and foreign students and between students in different years of study in all the questioned issues – choice of medical specialization, participation in classes which were helpful in decision making and necessity of counseling in choosing specialization. Conclusion. The results of the study clearly indicate that most of medical students have problem with choosing medical specialty. Guidance is not realized among most of students, despite the fact that the vast majority of them reports need for that kind of consultation.